Representational competence of Form Four science students on basic chemical concepts / Sim Joong Hiong - Sim, Joong Hiong (2010)
The general purpose of this study was to investigate Form four science students’ representational competence on basic chemical concepts. The main aims of the study were: (i) to investigate students’ understanding of basic chemical concepts, (ii) to evaluate their understanding of chemical representations, (iii) to assess their representational competence in chemistry, and (iv) to examine the influence of selected cognitive variables on their representational competence. A total of 411 Form four science students from seven urban secondary schools in Perak participated in this study. Data was obtained from seven instruments consisting of five paper-and-pencil tests, one questionnaire and interviews. The Statistical Package for the Social Sciences (SPSS) was used to analyze quantitative data collected. The main findings of this study were: Mean scores for the Test of Chemical Concepts (TCC), Test of Chemical Representations (TCR) and Test of Representational Competence (TRC) were respectively 13.68 (45.60%), 18.63 (51.75%), and 16.90 (42.25%). Students with a high level of understanding of (a) chemical concepts, and (b) chemical representations, had significantly higher overall level of representational competence compared to both the medium and the low groups, at p<0.001. However, students with medium and low levels of understanding of (a) chemical concepts, and (b) chemical representations, showed no significant difference in their overall levels of representational competence. Percent alternative conceptions for 18 of the 30 items in the TCC exceeded 50%; mean or percent mean alternative conceptions for all five categories of the most basic chemical concepts exceeded 50%. Percent alternative conceptions for 13 of the 36 items in the TCR exceeded 50%; the content domain with the highest percent mean alternative conception were `the three levels of representation of matter’ (71.93%), Percent difficulty for 23 of the 40 items in the TRC exceeded 50%; the category with the highest percent mean difficulty was the ability to translate between different representations across levels (78.83%). All the nine participants in the interviews were unfamiliar with the term `chemical representations’. However, participants from the 1High group gave correct examples of chemical representations while participants from the 2Low group totally had no idea about chemical representations. Participants from the Low group held a macroscopic view of matter, focused on the surface features of representations and used representations as depictions. Their ability to interpret or generate representations of chemical concepts, and to translate between representations, is limited; Participants from the 3Medium group had a microscopic view of matter. Microscopic terms were used only when prompted, and chemical representations were sometimes incorrectly used; Participants from the High group had both a macroscopic view and a microscopic view of matter, able to use microscopic terms appropriately and spontaneously, could generate submicroscopic representations using correct chemical representations, and able to translate fluently between representations. None of the nine participants in the semi-structured interviews could use multiple levels of representations in their description. The representational competence levels of the nine participants were: three at level 1, three at level 2, two at level 3, and one at Level 4. The regression model with three independent variables explains almost 71% of the variance of representational competence (prior knowledge ≈58%, developmental level ≈14%). The best predictor of representational competence is `understanding of chemical concepts’ or prior knowledge I, which alone accounts for 55.5% of the variance. The regression model was a good fit. The overall relationship was significant, [F (3, 188) = 156.405, p < 0.001]. Arising from the findings, some implications and recommendation were discussed, and further research suggested.